COMPARATIVE STUDY IN ARABIC AND ENGLISH TOWARD SYNTACTIC ANALYSIS CASE STUDY OF SUURAH AL-ZALZALAH AND ITS ENGLISH TRANSLATION - Nurfazriah, Nida; Alhadi, Ahmad Bakri (Arabi : Journal of Arabic Studies, 2019)
This paper presents the comparative study of Arabic and English with the syntactic analysis case study of Surah Al- Zalzalah and its English translation. In analyzing  Arabic and English structures, the writes used theories related to Arabic and English syntax. Then, the writer analyzed the method of translation with the translation methods stated by Newmark in this surah based on the knowing of the similarities and the differences of Arabic and English structures. In this study, the researcher used the descriptive-qualitative method. After analyzing the data of surah with its English translation consisting of eight verses, it was found that six verses had differences and two verses have similarities. By knowing the result of syntactic analysis, the analysis of the diction, the chosen appropriate meanings and the flexibility of English translation, the writer stated that the translation method used in this suurah is semantic method.